ANALISIS PENGARUH SELF-LEADERSHIP, WORKPLACE WELL BEING DAN PENGEMBANGAN KARIR TERHADAP EMPLOYEE ENGAGEMENT PADA INDUSTRI JASA - Muhammad Zakaria; Andy Ismail; Tyahya Whisnu Hendratni; Flora Grace Putrianti; Adi Soeprapto; Fatimah Malini Lubis (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the influence of self-leadership, workplace well-being, and career development on employee engagement in the service industry. The service sector faces significant challenges in maintaining employee engagement due to the nature of the work, which demands excellent service and intensive human interaction. In this context, self-leadership is considered crucial in encouraging individual initiative and responsibility, workplace well-being plays a role in maintaining working conditions that support mental and physical health, while career development provides motivational support for employees to achieve their long-term goals. This research uses a quantitative approach with a survey method involving 100 respondents working in the service sector. The data were analyzed using multiple linear regression to examine both the simultaneous and partial effects of the three independent variables on employee engagement. The results show that all three independent variables significantly influence employee engagement, both partially and simultaneously. Self-leadership demonstrated the strongest influence, followed by workplace well-being and career development. These findings imply that improving employee engagement in the service industry can be achieved by enhancing personal leadership capabilities, creating a work environment that supports well-being, and providing clear and sustainable career development paths. This study contributes to the development of employee engagement theory in the service sector and serves as a reference for human resource managers in designing effective engagement strategies.